The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41419-023-06320-y
|View full text |Cite|
|
Sign up to set email alerts
|

Human frataxin, the Friedreich ataxia deficient protein, interacts with mitochondrial respiratory chain

Davide Doni,
Federica Cavion,
Marco Bortolus
et al.

Abstract: Friedreich ataxia (FRDA) is a rare, inherited neurodegenerative disease caused by an expanded GAA repeat in the first intron of the FXN gene, leading to transcriptional silencing and reduced expression of frataxin. Frataxin participates in the mitochondrial assembly of FeS clusters, redox cofactors of the respiratory complexes I, II and III. To date it is still unclear how frataxin deficiency culminates in the decrease of bioenergetics efficiency in FRDA patients’ cells. We previously demonstrated that in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The deficiency of FXN in human cells has been shown to mainly impact mitochondrial complex I [40], which, among the respiratory complexes, has a higher turnover rate and is particularly prone to intrinsic degradation and oxidative damage [57]. In this regard, it has been observed that the exogenous expression of recombinant Nqo15 in FRDA patients' cells is able to ameliorate the respiratory phenotype [40]; the extent of this effect is comparable to what is observed by re-expressing FXN in these cells, indirectly supporting the hypothesis that FXN could play a key role in mitochondrial complex I proteostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deficiency of FXN in human cells has been shown to mainly impact mitochondrial complex I [40], which, among the respiratory complexes, has a higher turnover rate and is particularly prone to intrinsic degradation and oxidative damage [57]. In this regard, it has been observed that the exogenous expression of recombinant Nqo15 in FRDA patients' cells is able to ameliorate the respiratory phenotype [40]; the extent of this effect is comparable to what is observed by re-expressing FXN in these cells, indirectly supporting the hypothesis that FXN could play a key role in mitochondrial complex I proteostasis.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that, in healthy human cells, FXN is associated with mitochondrial cristae, the subcompartment that houses the respiratory chain [39]. The raison d'être of this enrichment lies in the ability of FXN to functionally interact with respiratory complexes I, II and III, as demonstrated by combining different experimental approaches [40]. Remarkably, the decrease in FXN in FRDA cells has been shown to lead to the more severe impairment of complex I than complexes II and III, suggesting that FXN could have a specific role in the stabilization and/or functioning of the first complex of the respiratory chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation